Bio-inspired hierarchical polymer micro- and nanostructures for anti-adhesion applications - Plamadeala, Cristina; Lifka, Sebastian; Buchberger, Gerda; Baumgartner, Werner; Heitz, Johannes (Frontiers in Materials, 2023)
In this paper we present polymer surfaces inspired by the calamistrum of cribellate spiders. The calamistrum resembles a micro-comb with a finger-print-like nanorippled topography, which allows cribellate spiders to handle and process nanofibers, without sticking to them. Due to its morphology, the calamistrum has a reduced surface for contact with the nanofibers, which therefore reduces the adhesive forces. Three different types of structured surfaces were prepared: nanostructured surfaces (ripples), microstructured surfaces (lines), and a combination of micro- and nanostructured surfaces (lines superimposed with ripples). Polymer lines were created using UV mask lithography. Nanoripples, i.e., laser-induced periodic surface structures, were fabricated by exposure to a KrF* laser beam. Nanofibers were produced and deposited onto each sample by electrospinning. To quantify each samples’ adhesiveness, a peel-off test was used, and the results were plotted and compared against the control samples–a flat polymer film. Our results indicate that lines have a stronger influence on the adhesion reduction than the nanoripples: nanoripples reduce fiber adhesion by 7%, whereas the lines reduce it by 28%. The highest adhesion reduction of 33% is obtained for the polymer surfaces with a combination of both lines and nanoripples. Our results open new insights in the field of artificial nanofiber adhesion on micro- and nanopatterned surfaces, which are essential when designing tools for nanofiber handling.